A Canadian, retrospective, multicenter experience with selexipag for a heterogeneous group of pediatric pulmonary hypertension patients - David Youssef; Susan Richards; Sabine Lague; Catherine Sheppard; Jenna Smith; Erika Vorhies; Martin Hosking; Matthew Pietrosanu; Angela Bates; Angela Bates (Frontiers Media S.A., 2023)
IntroductionSelexipag, an oral nonprostanoid prostaglandin receptor agonist, has led to reduced morbidity and mortality in adults with pulmonary arterial hypertension (PAH). While the adult literature has been extrapolated to suggest selexipag as an oral treatment for severe pediatric pulmonary hypertension (PH), longitudinal, multicenter data on the benefits of selexipag in this population are lacking. The purpose of this study is to present a longitudinal, multicentre experience with selexipag in a relatively large cohort of pediatric PH patients and add to the existing selexipag literature.Materials and methodsWe performed a retrospective, multicenter review describing the clinical outcomes of pediatric PH patients receiving selexipag in addition to standard oral pulmonary vasodilator therapy across three Canadian centers between January 2005 and June 2021.ResultsTwenty-four pediatric patients (fifteen female) with a mean age of 9.7 (range 2.0-15.5) years were included. Of this cohort, eighteen (75.0%) were in group 1, one (4.2%) was in group 2, four (16.7%) were in group 3, and one (4.2%) was in group 4. Twenty-two (91.7%) patients were on dual PH therapy after six months. Dosing was targeted to achieve 20-30 mcg/kg/dose orally every twelve hours. Median dose after twelve months was 30 mcg/kg/dose. Twelve months following selexipag initiation, median decreases of 0.2 cm in tricuspid annular plane systolic excursion, 3.5 mmHg in right-ventricular systolic pressure, and 6.1 mmHg in mean pulmonary arterial pressure were observed; none of these changes were statistically significant. Three patients died, one clinically deteriorated and required admission to a pediatric intensive care unit, ten had gastrointestinal symptoms, and three had flushing.ConclusionSelexipag appears to be a safe and effective adjunctive therapy for pediatric PH patients and has a tolerable adverse effect profile aside from gastrointestinal disturbances. Additional prospective studies of changes in hemodynamics and functional classification over a longer period and with a larger sample are needed. Future research should aim to identify subgroups that stand to benefit from the addition of selexipag as well as optimal timing and dosing for the pediatric population.